2003
DOI: 10.1021/ie0206498
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Polymaleimide

Abstract: Simplified syntheses of polymaleimide employing anionic polymerization (from the melt and from solution) and metal compound-alcohol initiators such as PbO, SnO, tin bis(2-ethyl hexanoate) in the presence of tert-butyl benzyl alcohol are presented. The resulting polymers contain a combination of C-N-and C-C-connected monomers. Preliminary structures of the polymers were determined using NMR spectroscopy. The ratio of C-N-and C-C-connected monomers was determined, and the percentage of C-N-connected monomer unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…On the other hand, numerous previous studies (e.g. Agarwal et al, 2003;Lakshminarayanan et al, 2003) have demonstrated that vaterite can form in the presence of macro organic molecules such as PVA (poly vinyl-alcohol) and PAA (poly acrylic-acid) that are rich in hydroxyl and carboxyl groups. It is highly possible that hydroxyl and carboxyl rich compounds are available in the supernatant solutions because B. megaterium can produce plenty of EPS, which is known to contain compounds rich in hydroxyl and carboxyl functional groups (see Omoike and Chorover, 2004).…”
Section: Formation Of Vaterite In Supernatant Solutionsmentioning
confidence: 99%
“…On the other hand, numerous previous studies (e.g. Agarwal et al, 2003;Lakshminarayanan et al, 2003) have demonstrated that vaterite can form in the presence of macro organic molecules such as PVA (poly vinyl-alcohol) and PAA (poly acrylic-acid) that are rich in hydroxyl and carboxyl groups. It is highly possible that hydroxyl and carboxyl rich compounds are available in the supernatant solutions because B. megaterium can produce plenty of EPS, which is known to contain compounds rich in hydroxyl and carboxyl functional groups (see Omoike and Chorover, 2004).…”
Section: Formation Of Vaterite In Supernatant Solutionsmentioning
confidence: 99%
“…In the first step 3-(N-maleimidyl)benzoic acid which was prepared by reaction of 3-amino benzoic acid with maleic anhydride in glacial acetic acid was used as starting material that introduced in acid-catalyzed esterification reaction with ethanol producing compound1(1) which inturn was introduced in reaction with hydrazine hydrate producing hydrazide (2). Introducing of compound (2) in acid catalyzed condensation reaction [19] with different aldehydes and ketones in the third step produced several new maleimide monomers (3-7) substituted with Schiff base moieties at meta-position.…”
Section: Al-azzawi and Faiqmentioning
confidence: 99%
“…Polymaleimides represent a class of rigid polymers having excellent thermal stability, high mechanical and electrical properties beside good chemical resistance [1][2][3]. In spite of all these properties, poor solubility and processability limit the applications of polyimides [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, PMAI was used by Ganjadhara et al to prepare nonlinear optical materials as liquid crystals to improve their thermal properties [ 1 ]. Generally, PMAI is synthesized by two approaches: one is homopolymerization of maleimide by free radical or anionic polymerization [ 2 , 3 ]. The other is thermolysis [ 4 ] or hydrolysis [ 5 ] of substituted maleimide homopolymers.…”
Section: Introductionmentioning
confidence: 99%